Emerging Plant Thermosensors: From RNA to Protein - Lin, J.; Xu, Y.; Zhu, Z.
How plants sense temperature is an important question. Here, we highlight recent achievements in identifying plant thermosensors, including RNA switch and protein-DNA binding ability. Finally, we borrow an idea from one recent mammalian study and propose a putative temperature-sensitive kinase as a thermosensory mechanism.
Keywords: RNA THERMOSENSOR; EVENING COMPLEX; ALTERNATIVE SPLICING; DNA BINDING